The Regulation of Exosome-Derived miRNA on Heterogeneity of Macrophages in Atherosclerotic Plaques - Li, Ximing; He, Xinyong; Wang, Junyan; Wang, Dan; Cong, Peiwei; Zhu, Aisong; Chen, Wenna (Frontiers in Immunology, 2020)
Exosomes are nanosized vesicles secreted by most cells, which can deliver a variety of functional lipids, proteins, and RNAs into the target cells to participate in complex intercellular communications. Cells respond to certain physical, chemical, and biological stimuli by releasing exosomes. Exosomes are rich in small molecules of RNA, including miRNAs and mRNAs, which have been demonstrated to have certain functions in recipient cells. Recent studies on single-cell RNA sequences have revealed the transcription and the heterogeneity of macrophages in Ldlr-/-mice fed with a high-fat diet. Five macrophage populations were found in the atherosclerotic plaques. It is worth noting that these subset populations of macrophages seem to be endowed with different functions in lipid metabolism and catabolism. A total of 100 differentially expressed mRNAs were selected for these subset populations. Importantly, these macrophage populations were also present in human advanced atherosclerosis. To clarify the specific functions and the regulatory mechanism of these macrophage populations, we extracted exosome RNAs from the plasma of patients with chronic coronary artery disease (CAD) and performed RNA sequencing analysis. Compared with the healthy control, a total of 14 miRNAs were significantly expressed in these patients. A total of 5,248 potential mRNAs were predicted by the bioinformatics platform. Next, we determined the outcome of the intersection of these predicted mRNAs with 100 mRNAs expressed in the above-mentioned five macrophage populations. Based on the screening of miRNA–mRNA pairs, a co-expression network was drawn to find out the key RNAs. Three down-regulated miRNAs and five up-regulated mRNAs were selected for validation by real-time RT-PCR. The results showed that the expression of miR-4498 in plasma exosomes was lower than that in the healthy control, and the expressions of Ctss, Ccr2 and Trem2 mRNA in peripheral blood mononuclear cells isolated from CAD patients were higher. In order to clarify the regulatory mechanism, we established a co-culture system in vitro. Studies have shown that the uptake of exosomes from CAD patients can up-regulate the expression of Ctss, Trem2, and Ccr2 mRNA in THP-1 cells induced by lipopolysaccharide. Our findings revealed a unique relationship between the transcriptional signature and the phenotypic heterogeneity of macrophage in the atherosclerotic microenvironment.